Polysaccharide from vinegar baked radix bupleuri as efficient solubilizer for water-insoluble drugs of Chinese medicine. (1st February 2020) - Zhao, Ya; Wan, Peng; Wang, Jinqiu; Li, Ping; Hu, Qiaohong; Zhao, Ruizhi
Graphical abstract: Highlights: VBCP-3-A was firstly isolated from VBCP as a potential solubilizer with high safety. Its solubilization effect on baicalin and rhein was far better than Tween 80. VBCP-3-A could self-assemble to form micelle-like aggregates in aqueous solution. VBCP-3-A improved oral bioavailability of baicalin and rhein. Abstract: The development of solubilizers with high efficiency, high safety and simple technology is one of the important fields in modern pharmaceutical industry. Our previous study found that vinegar baked Radix Bupleurum polysaccharides (VBCP) was a potential candidate. This study aimed to clarify which polysaccharide in VBCP had solubility enhancement effect and its solubilizing mechanism. Here, we reported that a novel acidic branched polysaccharide from VBCP, VBCP-3-A, which was non-toxic and had high solubility to baicalin and rhein. It was much better than that of Tween 80. The solubilization mechanism might be that VBCP-3-A self-assembled to form micelle-like aggregates in water, which can encapsulate water-insoluble constituents through the interaction of both hydrogen bonding and hydrophobic forces. in vivo pharmacokinetic study showed that VBCP-3-A increased Cmax and AUC (0-t) of baicalin and rhein. Those results suggested that VBCP-3-A was a potential solubilizer with high efficiency and high safety.